IISA 2014, the 5th International Conference on Information, Intelligence, Systems and Applications 2014
DOI: 10.1109/iisa.2014.6878826
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fast handovers for PMIPv6 in vehicular environments

Abstract: In modern wireless networking technologies, the need to support the nodes mobility is growing rapidly. This need is even greater in vehicular environments, in which the nodes are characterized by high mobility. In this paper, we study the basic protocols for mobility support in vehicular environments, such as Fast Handovers for Proxy Mobile IPv6 (PMIPv6) and TransientBinding for PMIPv6, and analyze the handover delay and their performance. Moreover, we present vehicular environment scenarios in which the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The proposed scheme employed neighbor MAGs information and GPS aided to vehicles in order to predict the candidate MAGs. Additionally, a temporary binding between NMAG and LMA to accelerate the handover procedure for ePFMIPv6 has been proposed in [37]. However, the results showed that the scheme is appropriate for low speed only-not more than 50 km/h.…”
Section: Intra Domain Handover Solutionsmentioning
confidence: 90%
See 1 more Smart Citation
“…The proposed scheme employed neighbor MAGs information and GPS aided to vehicles in order to predict the candidate MAGs. Additionally, a temporary binding between NMAG and LMA to accelerate the handover procedure for ePFMIPv6 has been proposed in [37]. However, the results showed that the scheme is appropriate for low speed only-not more than 50 km/h.…”
Section: Intra Domain Handover Solutionsmentioning
confidence: 90%
“…To overcome this limitation, few solutions have been proposed in [36][37][38] as an extension of PFMIPv6 protocol. The authors in [36] proposed a scheme called enhanced PFMIPv6 (ePFMIPv6) scheme.…”
Section: Intra Domain Handover Solutionsmentioning
confidence: 98%
“…Then, the current AP exchanges parameters with the target AP and the mobile user to the start session between them. When the packets are delivered to the previous AP, it buffers them using a tunneling session [ 38 , 39 , 40 , 41 , 42 ]. One of the most common tunneling protocols is MultiProtocol Label Switching (MPLS).…”
Section: Related Workmentioning
confidence: 99%
“…Up to date, mobile IP has been intensively investigated [15−17] . To reduce delay, the Fast MIPv6 (FMIPv6) protocol [18] and the enhanced FMIPv6 [19,20] handle net-work layer handoff operations prior to the MN's attachment to the new MAG. Our previous work [21] used the Extended service set (ESS)-based architecture to implement PMIPv6 in WLAN, in which the entity MAG-AP was introduced to reduce handoff delay.…”
Section: Related Workmentioning
confidence: 99%